Inhibition of P-Glycoprotein and Multidrug Resistance-Associated Protein 2 Regulates the Hepatobiliary Excretion and Plasma Exposure of Thienorphine and Its Glucuronide Conjugate - Kong, Ling-Lei; Shen, Guo-Lin; Wang, Zhi-Yuan; Zhuang, Xiao-Mei; Xiao, Wei-Bin; Yuan, Mei; Gong, Ze-Hui; Li, Hua (Frontiers in Pharmacology, 2016)
Thienorphine (TNP) is a novel partial opioid agonist that has completed phase II clinical evaluation as a promising drug candidate for the treatment of opioid dependence. Previous studies have shown that TNP and its glucuronide conjugate (TNP-G) undergo significant bile excretion. The purpose of this study was to investigate the roles of efflux transporters in regulating biliary excretion and plasma exposure of TNP and TNP-G. An ATPase assay suggested that TNP and TNP-G were substrates of P-gp and MRP2, respectively. The in vitro data from rat hepatocytes showed that bile excretion of TNP and TNP-G was regulated by the P-gp and MRP2 modulators. The accumulation of TNP and TNP-G in HepG2 cells significantly increased by the treatment of mdr1a or MRP2 siRNA for P-gp or MRP2 modulation. In intact rats, the bile excretion and pharmacokinetic profiles of TNP and TNP-G were remarkably changed with tariquidar and probenecid pretreatment, respectively. Tariquidar increased the Cmax and AUC0-t and decreased MRT and T1/2 of TNP, whereas probenecid decreased the plasma exposure of TNP-G and increased its T1/2. Knockdown P-gp and MRP2 function using siRNA significantly increased the plasma exposure of TNP and TNP-G and reduced their mean retention time in mice. These results indicated the important roles of P-gp and MRP2 in hepatobiliary excretion and plasma exposure of TNP and TNP-G. Inhibition of the efflux transporters may affect the pharmacokinetics of TNP and result in a drug-drug interaction between TNP and the concomitant transporter inhibitor or inducer in clinic.